Network analysis of the metabolome and transcriptome reveals novel regulation of potato pigmentation. (4th January 2016) - Cho, Kyoungwon; Cho, Kwang-Soo; Sohn, Hwang-Bae; Ha, In Jin; Hong, Su-Young; Lee, Hyerim; Kim, Young-Mi; Nam, Myung Hee
Highlight: An integrated approach of metabolomics and transcriptomics was applied to understand regulatory networks associated with biosynthesis of anthocyanins that are differentially regulated in light-red- and dark-purple-colored potato cultivars. Abstract: To gain insights into the regulatory networks related to anthocyanin biosynthesis and identify key regulatory genes, we performed an integrated analysis of the transcriptome and metabolome in sprouts germinated from three colored potato cultivars: light-red Hongyoung, dark-purple Jayoung, and white Atlantic. We investigated transcriptional and metabolic changes using statistical analyses and gene–metabolite correlation networks. Transcript and metabolite profiles were generated through high-throughput RNA-sequencing data analysis and ultraperformance liquid chromatography quadrupole time-of-flight tandem mass spectrometry, respectively. The identification and quantification of changes in anthocyanin were performed using molecular formula-based mass accuracy and specific features of their MS 2 spectra. Correlation tests of anthocyanin contents and transcriptional changes showed 823 strong correlations (correlation coefficient, R 2 >0.9) between 22 compounds and 119 transcripts categorized into flavonoid metabolism, hormones, transcriptional regulation, and signaling. The connection network of anthocyanins and genes showed a regulatory system involved in the pigmentation of light-red Hongyoung and dark-purple Jayoung potatoes, suggesting that this systemic approach is powerful for investigations into novel genes that are potential targets for the breeding of new valuable potato cultivars.